Changes in Travel Behaviour During the Pandemic: Exploring Why Public Transport is Not Back to Pre-Pandemic Levels - Susanne T. Dale Nordbakke (Findings, 2022)
This study explores why shares using public transport in autumn 2021 remained well below 2019 pre-pandemic levels, even after most COVID-19 restrictions had been lifted. Based on an interview survey of 1145 workers in the Oslo region in Norway, the study offers evidence in support of four potential explanations: increased levels of remote working; fear of infection on public transport; changes in transport mode preferences; and ticket solutions that are poorly suited to new hybrid work patterns. In addition, the study suggests public transport is taking a double hit by increased remote working. Not only do fewer people travel to work by public transport, but those who can work remotely previously used public transport more before the pandemic compared to those who cannot work remotely.